PERAN ORANG TUA TERHADAP PERKEMBANGAN KEPRIBADIAN ANAK USIA DINI - Maria Aprilianti Beo; Marsianus Meka; Andi Nafsia; Konstantinus Dua Dhiu (Jurnal Santiaji Pendidikan (JSP), 2026)
The purpose of this study was to determine the relationship between parental involvement and early childhood personality development, describe the level of children's personality development, and identify the most influential parental involvement factors.This study used qualitative methods with a descriptive approach. Data were collected through interviews, observations, and documentation to obtain in-depth information about the forms of parental involvement and their influence on children's self-confidence, independence, and social-emotional skills.The study subjects included five early childhood children at the Lebijaga Satu Atap Kindergarten (TKK Satu Atap), with informants consisting of parents, teachers, and children. The study was conducted in Lebijaga Village in September 2025, aligning with school and family activities. Based on the results, the level of parental involvement was categorized as good to very good. Children who received continuous parental involvement demonstrated better personality development, particularly in self-confidence, independence, and social-emotional skills. Parental involvement, manifested through mentoring in learning activities, providing motivation, positive communication, and collaboration with teachers, plays a crucial role in supporting early childhood personality development.